2014
DOI: 10.3923/ajar.2014.234.247
|View full text |Cite
|
Sign up to set email alerts
|

Mutation Breeding of Maize for Anticipating Global Climate Change in Indonesia

Abstract: This article focused on the analysis of the study paradigm changes in one of historical subjects in Indonesia University of Education. Nowadays, historical study only focused on human activities in the past without seeing the human interactions with nature, and how the nature reacts to human being. It means that historical study which evolves nowadays is using anthropocentric paradigm which placed human being as the centre of life. Various disasters that happened should change the way people see anthropocentri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…Some of the lines in the collection have been described in previous studies, viz. Ruswandi et al (2014) reported some maize genotypes showing early maturity and also drought tolerance. Some maize hybrid formation showed high yield (Ruswandi et al, 2015a, b).…”
Section: Asian J Cropmentioning
confidence: 99%
See 1 more Smart Citation
“…Some of the lines in the collection have been described in previous studies, viz. Ruswandi et al (2014) reported some maize genotypes showing early maturity and also drought tolerance. Some maize hybrid formation showed high yield (Ruswandi et al, 2015a, b).…”
Section: Asian J Cropmentioning
confidence: 99%
“…Indonesia is among the important world maize producer in South East Asia (Ruswandi et al, 2014). Some of the problems encountered in maize development in Indonesia are the conversion of fertile land under maize production into industrial and residential areas, drought due to global climate change, displacement of maize planting area to marginal land including forest and others.…”
Section: Introductionmentioning
confidence: 99%
“…Crop Sci., 7 (3): 160-173, 2015 MATERIALS AND METHODS Genetic materials: The genetic materials were evaluated in the study included forty six mutant lines; one hundred and thirty eight single cross hybrids derived from line×tester crosses of fourty six mutant lines to three tester lines and three tester lines. The forty six mutant lines and three tester lines were developed previously by Ruswandi et al (2014). Crosses were made during 2013 and the evaluation of genotypes in experimental trials were performed during the rainy season of 2014 at the experimental plots of Faculty of Agriculture, Padjadjaran University, in Arjasari, Bandung, West Java, Indonesia.…”
Section: Asian J Cropmentioning
confidence: 99%
“…Ruswandi et al (2014) developed new mutant lines for breeding program of maize in Indonesia using gamma irradiation. They reported some maize mutant lines showing early maturity and also drought tolerance.…”
Section: Introductionmentioning
confidence: 99%
“…With the recent advances in science, molecular breeding has become a key approach for crop improvement and maize has benefitted the most. Common approaches employed in molecular research include marker assisted selection, marker assisted backcross, GMO and mutation breeding (Ruswandi et al, 2014;Waminal et al, 2013;Ye et al, 2009;Collard et al, 2005). For a successful molecular breeding, a mapping population developed from two contrasting homozygous or near isogenic parents is used (Xu, 2010;Semagn et al, 2006b;Landi et al, 2005).…”
Section: Molecular Breedingmentioning
confidence: 99%